Brief Report: Long‐Term Assessment of Fibromyalgia in Patients With Culture‐Confirmed Lyme Disease1. Issue 3 (March 2015) - Wormser, Gary P.; Weitzner, Erica; McKenna, Donna; Nadelman, Robert B.; Scavarda, Carol; Farber, Shimon; Prakash, Priya; Ash, Julia; Nowakowski, John
<x xml:space="preserve">Abstract</x> Objective Fibromyalgia (FM) occurs in 2–8% of the general population, and one of the triggers may be Lyme disease. The aim of this study was to evaluate for FM in patients with culture‐confirmed Lyme disease. Methods Patients with culture‐confirmed Lyme disease who originally presented with erythema migrans were enrolled in a prospective study between 1991 and 2000 and have been evaluated annually to determine their long‐term outcomes. In 2011–2013, the patients were evaluated for FM, by both interview and tender point examination. Results Among the 100 patients assessed, 52% were male, and the mean age was 64.9 years (median 64 years [range 42–86 years]). The mean duration of followup was 15.4 years (median 16 years [range 11–20 years]). At least 24 of the patients (24%) had experienced a second episode of erythema migrans before being evaluated for fibromyalgia. One patient (1% [95% confidence interval 0.025–5.4%]) met the criteria for fibromyalgia. In this patient, the symptoms consistent with fibromyalgia began >19 years after Lyme disease was diagnosed. Conclusion Fibromyalgia was observed in only 1% of 100 patients with culture‐confirmed early Lyme disease; this frequency is consistent with that observed in the general population.